Analysis of Strategies of School Leaders in Increasing Students’ Learning Achievement at Sekolah Dasar Islam Terpadu AlAzhar Rautauprapat - Galih Orlando; Sahbuki Ritonga; Mulkan Darajat; Rendi Fitra Yana; Yunita Sipahutar (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this research. 1) Know how to plan, 2) organize, 3) implement, 4) control and limit the principal's management process to improve student learning outcomes at Al Azhar Rautauprapat Islamic Elementary School. This research was conducted at the Integrated Islamic Elementary School Al Azhar Rautauprapat, this type of research is qualitative research. The approach in this study uses a qualitative descriptive approach. The informants of this study were school principals, vice principals, lecturers, staff and students. Data collection is based on the method of observation, questions and answers, and documentation, and data analysis is done through data reduction, data presentation, and drawing conclusions. The results showed that: The implementation of the administrative role of the school principal to improve student learning outcomes in Al Azhar Rautauprapat Islamic Elementary School uses the Planning, Organization, Leadership and Control (POAC) method. There are two principal plans, namely: student planning through the preparation of lesson plans and extracurricular activities. Meanwhile, teacher planning provides training and guidance. Then the organization created by the customer must create all stakeholders in a good container. Then the client executes or drives the good container. The principal then implements or drives a platform to work together to develop the vision, mission and goals of the school. Finally, the director evaluates and evaluates all implemented programs. Leadership and Control (POAC) method. There are two principal plans, namely: student planning through the preparation of lesson plans and extracurricular activities. Meanwhile, teacher planning provides training and guidance. Then the organization created by the customer must create all stakeholders in a good container. Then the client executes or drives the good container. The principal then implements or drives a platform to work together to develop the vision, mission and goals of the school. Finally, the director evaluates and evaluates all implemented programs. Leadership and Control (POAC) method. There are two principal plans, namely: student planning through the preparation of lesson plans and extracurricular activities. Meanwhile, teacher planning provides training and guidance. Then the organization created by the customer must create all stakeholders in a good container. Then the client executes or drives the good container. The principal then implements or drives a platform to work together to develop the vision, mission and goals of the school. Finally, the director evaluates and evaluates all implemented programs. Then the organization created by the customer must create all stakeholders in a good container. Then the client executes or drives the good container. The principal then implements or drives a platform to work together to develop the vision, mission and goals of the school. Finally, the director evaluates and evaluates all implemented programs. Then the organization created by the customer must create all stakeholders in a good container. Then the client executes or drives the good container. The principal then implements or drives a platform to work together to develop the vision, mission and goals of the school. Finally, the director evaluates and evaluates all implemented programs.